ARTIFICIAL INTELLIGENCE ETHICS AND ITS LEGAL ASPECTS - Meliyeva Maftuna Sayduvaliyevna (Modern American Journals, 2025)
Artificial Intelligence (AI) has evolved from a niche research area into a transformative global technology impacting almost every sector of society. From autonomous vehicles and predictive analytics to facial recognition and natural language processing, AI’s capabilities raise new possibilities — and equally significant ethical and legal challenges. This paper explores the fundamental ethical principles guiding AI development, examines existing and emerging legal frameworks, and evaluates how these two domains interact in shaping responsible AI. Through a review of literature, case studies, and analysis of international regulations, the paper aims to present a comprehensive view of the intersection between AI ethics and law.
Keywords: Artificial Intelligence, Ethics, AI Law, Privacy, Accountability, Regulation.